Canopy spray deposition and related mortality impacts of commonly used insecticides on Drosophila suzukii Matsumura (Diptera: Drosophilidae) populations in blueberry. Issue 4 (5th December 2019) - Mermer, Serhan; Pfab, Ferdinand; Hoheisel, Gwen A; Bahlol, Haitham Y; Khot, Lav; Dalton, Daniel T; Brewer, Linda J; Rossi Stacconi, Marco V; Zhang, Chengzhu; Xue, Lan; Walton, Vaughn M
Abstract: BACKGROUND: Insecticide applications in blueberry production systems play a crucial role in the control of Drosophila suzukii populations. Here, quantitative spray deposition patterns were obtained under replicated field experiments in blueberry during two field seasons with three sprayers, i.e. cannon, electrostatic, and air‐blast. Seven insecticides were tested (at 6 hours using a Potter spray tower) to determine the mortality data for adult D. suzukii . Spray deposition and mortality data for adult D. suzukii were used to create model simulations for insect populations. Model simulations included field deposition rates of sprayers and insecticide mortality as factors. Simulations were applied in different combinations with five applications over a 6‐week period. RESULTS: Relative deposition rates for the cannon sprayer were elevated in the upper zones of the canopy, whereas for the air‐blast sprayer, deposition was greater in the bottom zones. Electrostatic spray deposition was relatively uniform within the six canopy zones. Clear trends in D. suzukii laboratory mortality were found with lowest to highest mortality recorded for phosmet, spinetoram, spinosad, malathion, cyantraniliprole, zeta‐cypermethrin, and methomyl respectively. Maximum D. suzukii population impacts, as shown by model outputs, were observed with air‐blast sprayers together with zeta‐cypermethrin. CONCLUSION: The electrostatic sprayer had the least variable canopy deposition among the three types of spray equipment, and the air‐blast sprayer had the highest overall deposition rates. This study provides new hypotheses that can be used for field verification with these spray technologies and insecticides as key factors. © 2019 Society of Chemical Industry Abstract : The greatest impact on a Drosophila suzukii population was found when using an air‐blast sprayer combined with zeta‐cypermethrin in blueberry.